2022
DOI: 10.3390/cancers14071796
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Sarcoma Study: Association of Genetic Alterations in the Apoptosis Pathways with Chemoresistance to Doxorubicin

Abstract: Soft tissue sarcomas (STS) are heterogeneous cancers with more than 100 histological subtypes, different in molecular alterations, which make its personalized therapy very complex. Gold standard of chemotherapy for advanced STS includes combinations of Doxorubicin and Ifosfamide or Gemcitabine and Docetaxel. Chemotherapy is efficient for less than 50% of patients and it is followed by a fast development of drug resistance. Our study was directed to the search of genetic alterations in cancer cells associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, management of STS is increasingly subtype-dependent and resistance for Dox is present. Resistance mediating molecular alterations such as the mutation of TP53 was discussed since p53-dependent apoptosis is the main mechanism of action of Dox ( 32 ).Unfortunately, the investigation of new molecular targets only showed an incremental progress and no superior effect relative to Dox ( 13 ). Nevertheless, patients with undifferentiated pleomorphic sarcoma (UPS, GCT cells) showed the highest overall response from treatment with monoclonal antibodies against PD-L1 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, management of STS is increasingly subtype-dependent and resistance for Dox is present. Resistance mediating molecular alterations such as the mutation of TP53 was discussed since p53-dependent apoptosis is the main mechanism of action of Dox ( 32 ).Unfortunately, the investigation of new molecular targets only showed an incremental progress and no superior effect relative to Dox ( 13 ). Nevertheless, patients with undifferentiated pleomorphic sarcoma (UPS, GCT cells) showed the highest overall response from treatment with monoclonal antibodies against PD-L1 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, GCT and RD cells showed a pronounced resistance to Dox treatment of any schedule, which can in part be explained by the mutated TP53 gene. In primary STS cultures, a high mutation rate in apoptotic signaling genes (TP53, ATM, PIK3CB, PIK3R1, NTRK1, CSF2RB) was found and linked to Dox resistance ( 32 ). Future experiments should include molecular analysis regarding apoptosis and migration biomarkers to understand the additive effects mediated by anthracycline-based regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, TP53 mutation in patients with breast cancer is associated with primary resistance to doxorubicin therapy [31]; the loss of functional p53 protein confers resistance to etoposide in neuroblastoma and glioma cells [32,33]. Moreover, transfection with wild-type p53 sensitizes soft tissue sarcoma cells to doxorubicin [34]. Considering these previous observations and the present study, it is suggested that p53 signaling regulates topoisomerase inhibitor sensitivity, supporting our results that p53 regulation via the nucleolar stress response is involved in topoisomerase inhibitor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained from some STS cell lines [5] are not in full agreement with the results of tumor analysis of STS patients [6]. Although the mutation rate is low in STS [7], a number of studies have revealed a relationship between the development of resistance to Dox and the presence of mutations in the apoptosis activation pathway [8]. It has been found that in ChT-resistant STS samples, the expression of genes involved in signaling pathways associated with cell adhesion, migration, proliferation, cytotaxis, and phagocytosis, as well as signaling cascades PI3K-Akt, NF-κB, MAPK, and Jak -STAT is activated.…”
Section: Introductionmentioning
confidence: 99%